Simulasi Monte Carlo Untuk Memprediksi Persediaan Darah - Ilham, Wanda; Syafrinal, Ilwan (Fakultas Komputer - Universitas Universal, 2024)
Blood is a combination of plasma and cells that circulate throughout the body, functioning to distribute oxygen and nutrients. Predicting the need for blood supplies at a certain time is a complex challenge because it is influenced by various factors such as the number of donors, patient demand, and the limited shelf life of blood. Monte Carlo simulation has emerged as a useful tool in modeling and predicting the state of complex systems. In the context of blood supply, Monte Carlo Simulation allows researchers and hospital administrators to identify optimal supply levels taking into account various existing variables and uncertainties. This method uses random numbers to simulate various scenarios that may occur in the future, helping in planning more accurately and responsively to changes in blood demand and supply. Thus, Monte Carlo Simulation plays an important role in ensuring sufficient blood availability, reducing the risk of shortages, and optimizing blood supply management in hospitals and blood transfusion units.